Remdesivir: an antiviral for the treatment of COVID‐19. Issue 7 (4th September 2020) - Chaplin, Steve
Abstract : The antiviral remdesivir (Veklury) is the first drug to be licensed for the treatment of COVID‐19. This article discusses its mode of action, indications, clinical trial efficacy and side‐effects.